Cysteine cathepsins: A long and winding road towards clinics. (December 2022) - Biasizzo, Monika; Javoršek, Urban; Vidak, Eva; Zarić, Miki; Turk, Boris
Abstract: Biomedical research often focuses on properties that differentiate between diseased and healthy tissue; one of the current focuses is elevated expression and altered localisation of proteases. Among these proteases, dysregulation of cysteine cathepsins can frequently be observed in inflammation-associated diseases, which tips the functional balance from normal physiological to pathological manifestations. Their overexpression and secretion regularly exhibit a strong correlation with the development and progression of such diseases, making them attractive pharmacological targets. But beyond their mostly detrimental role in inflammation-associated diseases, cysteine cathepsins are physiologically highly important enzymes involved in various biological processes crucial for maintaining homeostasis and responding to different stimuli. Consequently, several challenges have emerged during the efforts made to translate basic research data into clinical applications. In this review, we present both physiological and pathological roles of cysteine cathepsins and discuss the clinical potential of cysteine cathepsin-targeting strategies for disease management and diagnosis.